Taxonomic studies on Parahellenia (Costaceae) in Vietnam: a new species, P. trongduyii, and a new combination, P. candida - Chen, Juan; Nguyen, van Canh; Nguyen, van Khuong; Nguyen, Khang Sinh; Nuraliev, Maxim S.; Xia, Nianhe (Phytotaxa, 2023)
Parahellenia trongduyii, a new species of Costaceae from Vietnam, is described and illustrated. The new species is similar to P. tonkinensis, but differs in unbranched or barely branched stems, narrowly triangular-lanceolate glabrous buds, bract apex with a soft mucro, yellow to whitish yellow labellum with longitudinal orange to red lines at center, longer anther crest and stigma with a slightly bilobed dorsal appendage. A new combination, Parahellenia candida, is proposed for the species earlier known as Cheilocostus candidus. A key to Parahellenia in Vietnam is also provided.